Locomotor and metabolic activities of Gymnostreptus olivaceus (Diplopoda, Spirostreptida) at different photoperiod conditions - Boccardo, L.; Penteado, CHS (Elsevier B.V., 1995)
In the present investigation the locomotor and the metabolic activity of Gymnostreptus olivaceus were studied, using 24-hr cycles at different photoperiods and constant temperature and RH. Locomotor activity was studied by the actography method and was reported as coefficients of nocturnalism [CN (N/N + D). 100]. The results showed a nocturnalism coefficient of 98,71% under normal photoperiod conditions and of 29,58% under inverted photoperiod conditions. In constant illumination, the CN of G. olivaceus was 88,22%, and in constant darkness, its rhythm was close to that of the normal photoperiod (CN = 94,92%). The metabolic activity was studied by manometric Warburg respirometry and lit was reported as mu l O-2 . g(-1). h(-1). The respiratory rate of G. olivaceus under normal photoperiod condition was higher at night than during the day (52,52 x 28,76), coinciding with the pattern of nocturnal locomotor activity of the animal. However, under conditions of inverted photoperiod, the millipede maintained its tendency toward a more intense nocturnal respiratory rate (50,35 x 39,14). Similar behaviours were observed under constant illumination and constant darkness, in which G. olivaceus again presented higher nocturnal respiratory rates than diurnal ones(85,84 x 53,48 and 73,18 x 57,0, respectively). The present experimental data suggests the persistence of an endogenous rhythm where the light may not be an important exogenous synchronizer of the activity of G. olivaceus, because it was insufficient to block the start of the biological clock and the natural tendency of higher nocturnal activities of millipedes, principally when the tests were performed in constant illumination or darkness (free-running tests).
Keywords: diplopoda; millipedes; actography; locomotor activity; metabolism; respiratory rhythms; photoperiods; diurnal and nocturnal cycles